Morphology and nesting behavior of Ropalidia variegata variegata Smith 1852 (Hymenoptera: Vespidae) from District Mohmand, Khyber Pakhtunkhwa, Pakistan (Zoo Botanica, 2025)
This study was carried out in Mohmand District (Khyber Pakhtunkhwa, Pakistan) to investigate morphological identification and nest activities of a wasp species (Ropalidia variegata variegata). Wasp colonies were observed on mango tree foliage and monitored over a four-month period. Nest-building activity began at the center of the leaf and expanded along the midrib and lateral edges as the colony size increased. The numbers of nest cells, larvae, and total cells were recorded. Specimens were identified as R. variegata variegata using standard entomological keys. Distinct coloration patterns were noted on different body parts, including yellow, reddish-brown, and black hues. Morphometric measurements showed that the head measured 2.24 ± 0.2 mm in length and 1.96 ± 0.2 mm in breadth. The pronotum was rectangular, brown in color, and bordered by a distinct yellow margin. The thorax measured 3.51 ± 0.14 mm in length and 2.0 ± 0.42 mm in breadth. The second abdominal segment was bell-shaped. The legs measured 4.6 ± 0.56 mm in length and 0.1 ± 0.07 mm in width, while the wings measured 5.1 ± 0.8 mm in length.
Keywords: Ropalidia variegata variegate; behaviour; morphology; nesting; reproduction